2006
DOI: 10.1136/ard.2005.043299
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of combination etanercept and methotrexate versus etanercept alone in patients with rheumatoid arthritis with an inadequate response to methotrexate: the ADORE study

Abstract: Both the addition of ETN to MTX and the substitution of ETN for MTX in patients with rheumatoid arthritis who had an inadequate response to MTX resulted in substantial improvements in clinical signs and symptoms and were generally well-tolerated treatment strategies for improving clinical signs and symptoms of rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 23 publications
7
79
0
3
Order By: Relevance
“…Most AE observed during this study were not serious, and the incidence of serious AE (7.54%) was similar to that observed in clinical trials involving ETN (5% 16 , 7% 17 , and 11% 18 ). This surveillance showed that the most commonly observed AE was injection site reactions (5.3%), and the most frequently observed serious AE was pneumonia (0.8%).…”
Section: Discussionsupporting
confidence: 51%
“…Most AE observed during this study were not serious, and the incidence of serious AE (7.54%) was similar to that observed in clinical trials involving ETN (5% 16 , 7% 17 , and 11% 18 ). This surveillance showed that the most commonly observed AE was injection site reactions (5.3%), and the most frequently observed serious AE was pneumonia (0.8%).…”
Section: Discussionsupporting
confidence: 51%
“…As in other studies [13,14,15] parameters of disease activity such as ESR and disease activity score (DAS28) decreased after three months therapy with etanercept. Subsequent drug administrations caused further decrease of these parameters of disease activity (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…Several studies have shown that anti-TNF-α treatment with infliximab, a chimeric antitumour necrosis factor α antibody [11,12] and etanercept, a soluble tumour necrosis factor receptor (sTNFr) [13,14,15] diminish clinical activity of RA. In our previous report, we demonstrated that infusions of infliximab reduce serum chemokines concentrations in RA patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…The trial failed to demonstrate the superiority of continuing MTX rather than discontinuing it upon starting ETN therapy 5 . Because the ADORE trial was only 16 weeks, with a regimen of MTX tapering over the initial 4 weeks, there could be no marked difference between continuation versus discontinuation of MTX, if any difference at all.…”
mentioning
confidence: 99%